توظيف الأدب الإسلامي في خدمة الدعوة – نجيب الكيلاني أنموذجا - حشيفة, منى (University of Eloued جامعة الوادي, 2017)
تسلط هذه الدراسة الضوء على توظيف الأدب الإسلامي في خدمة الدعوة الإسلامية من خلال أعمال الأديب نجيب الكيلاني. و قد قسمت الدراسة إلى ثلاثة فصول ، مع مقدمة وخاتمة و كذا فهارس عامة ، فالفصل الأول يوضح الخطوات المنهجية المتبعة في ثنايا البحث و الفصل الثاني خصصته لدراسة الأدب الإسلامي مفهومه ونشأته و عوامل نشأته و خصائصه ، و توظيفه في عصر النبوة و عصر الصحابة و العلماء المعاصرين و الأدباء ، بينما الفصل الثالث فقد تناولت فيه الكلام عن نجيب الكيلاني : مولده ونشأته ، آثاره واتجاهه الإسلامي ، و حياته العلمية وثقافية ، و الحالة الاجتماعية والعلمية ، والجوائز التي حصل عليها ، و توظيفه للأدب الإسلامي في خدمة الدعوة من خلال أعماله كما تضمنت خاتمة البحث إلى أهم النتائج التي توصلت إليها من خلال الدراسة لهذه الشخصية الأدبية الدعوية This study sheds light on the use of Islamic literature in the service of Islamic da'wah through the work of the writer Najib al-Kilani. The survey is divided into three chapters in addition to an introduction conclusion and general appendices. The first chapter illustrates the steps of the methodology followed in this study and the second chapter is devoted for studying the Islamic literature its conception its inception Aswell as the factors that led to its inception its characteristics its employment during the prophecy era the companions era the contemporaneous and authors era . While the third chapter talks about Nagib Kaylani lis birth his inception his effects and Islamic views his xientific and social state the prizes hegot his employment of Islamic literature in the service of the call through his works .And the conclusion contains the essential findings we arrived at through our study of this literary character
مذكرة ماستر تخصص دعوة واعلام
Keywords: : الأدب ، الأدب الإسلامي ، الدعوة الإسلامية: Literature , liturature Islamic , Islamic da'wah